Neutrophil-to-Lymphocyte Ratio (NLR) and Platelet-to-Lymphocyte Ratio (PLR) Can Predict Spontaneous Preterm Birth? - Yuce E (Journal of Inflammation Research, 2023)
Ebru Yuce1,2 1Department of Gynecology and Obstetrics, Yuksek Ihtisas University, Faculty of Medicine, Ankara, Turkey; 2Department of Gynecology and Obstetrics, Liv Hospital, Ankara, TurkeyCorrespondence: Ebru Yuce, Department of Gynecology and Obstetrics, Yuksek Ihtisas University, Faculty of Medicine, Kavaklidere, Bestekar Cd No: 8, Cankaya, Ankara, 06680, Turkey, Tel +905327135990, Email dr.ebruk@gmail.comPurpose: To investigate the role of neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) in the prediction of spontaneous preterm birth.Patients and Methods: Data was retrospectively collected from hospital record between February 2018 and November 2022. Pregnant women (n = 78) with a single pregnancy between 24 and 34 weeks of gestation, presented with labor pain, and had regular uterine contractions (threatened preterm labor – TPL) were included. Patients delivered within the first week after TPL were included in group 1 (n = 40) and who delivered after in group 2 (n = 38). Two groups were investigated for NLR and PLR values.Results: The median cervical length among women who gave birth within a week was significantly lower (24.5 versus 30.0 p < 0.001). The median neutrophil-to-lymphocyte ratio among women who gave birth within a week was significantly higher (6.4 versus 4.5 p < 0.001). The median platelet-to-lymphocyte ratio among women who gave birth within a week was significantly higher (151 versus 131 p < 0.001). The cut-off values to predict preterm birth were > 5 for NLR (sensitivity: 90%, specificity: 92.1%), > 139 for PLR (sensitivity: 97.5%, specificity: 100%).Conclusion: NLR and PLR values predict spontaneous preterm birth with high sensitivity and specificity. By predicting preterm birth, the pregnancy process can be managed sensitively and smoothly.Keywords: neutrophil-lymphocyte ratio, NLR, platelet-lymphocyte ratio, PLR, preterm birth, prediction